Internship in sociology: a new dimension of increasing students’ employability in Malaysian job market - Mohamad Diah, Nurazzura; Abd Rahman, Khairulanuar; Mustari, Sohela; Ramli, Noor Syafika (IDOSI Publication, 2014)
High requirements of job market inclined universities of today to make internship training as part of theirgraduation pre-requisite. This study attempts to investigate the outcome of internship programme in the Sociology and Anthropology department (IIUM). Findings from this study explicitly show that internship among students from this discipline has essentially improved their soft skills and increased their work-place literacy and well-being. Despite the lack of information about this discipline as well as its practicality aspects by the industry, Sociology and Anthropology students are well accepted in both private and public sectors to undertake their internship training. Methodologically, this study was conducted to congregatethe opinions and experience about internship programme among Sociology and Anthropology students. Survey was used to collect required data from 100 students who have completed their three months internship either in the public or private sector. In general, internship is crucial, particularly among social science students as it enriches theirexperiences, knowledge and skills both in the personal and social life.